Optimization of cellobiohydrolase production and secretome analysis of Trametes villosa LBM 033 suitable for lignocellulosic bioconversion - Coniglio, Romina O. (2019)
The production of bioethanol from lignocellulosic biomass comprises the enzymatic hydrolysis of lignocellulosic structures by three major cellulases. Among them, cellobiohydrolases are considered to be key enzymes playing a significant role on cellulose degradation. The ability to produce lignocellulolytic enzymes by fungi such as Trametes villosa makes them appropriate degraders for large-scale applications. In this context, the aim of this study was to obtain and characterize a cellobiohydrolase-enriched extracellular extract of T. villosa LBM 033 (Misiones, Argentina), which is suitable for the enzymatic hydrolysis of lignocellulosic residues. The effect of carbon and nitrogen sources on cellobiohydrolase activity was evaluated using experimental designs and a culture medium was optimized to obtain a cellobiohydrolase-enriched extract suitable for the hydrolysis of lignocellulosic biomass. Moreover, by secretome analysis, nine enzymes involved in lignocellulosic biomass degradation were identified under the optimized conditions; among them is a cellobiohydrolase II from the glycosil-hydrolase 6 family.